2018
DOI: 10.1186/s12885-018-4551-y
|View full text |Cite
|
Sign up to set email alerts
|

A rare CHD5 haplotype and its interactions with environmental factors predicting hepatocellular carcinoma risk

Abstract: BackgroundCHD5 is a conventional tumour-suppressing gene in many tumours. The aim of this study was to determine whether CHD5 variants contribute to the risk of hepatocellular carcinoma (HCC).MethodsGene variants were identified using next-generation sequencing targeted on referenced mutations followed by TaqMan genotyping in two case-control studies.ResultsWe discovered a rare variant (haplotype AG) in CHD5 (rs12564469-rs9434711) that was markedly associated with the risk of HCC in a Chinese population. A log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In the present study, we first demonstrated that CHD5 was differentially expressed between most cancer tissues and the adjacent normal tissues, which suggested that CHD5 was a potential tumor suppressor gene in most cancers. The above finding was consistent with previously reported results regarding the differential expression of CHD5 in different cancers, including neuroblastoma, melanoma, hepatocellular carcinoma, non-small cell lung cancer, and head and neck squamous cell carcinoma [ 20 , 21 , 22 , 23 , 24 ]. Our results also showed that the expression of CHD5 was upregulated in some cancer types.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we first demonstrated that CHD5 was differentially expressed between most cancer tissues and the adjacent normal tissues, which suggested that CHD5 was a potential tumor suppressor gene in most cancers. The above finding was consistent with previously reported results regarding the differential expression of CHD5 in different cancers, including neuroblastoma, melanoma, hepatocellular carcinoma, non-small cell lung cancer, and head and neck squamous cell carcinoma [ 20 , 21 , 22 , 23 , 24 ]. Our results also showed that the expression of CHD5 was upregulated in some cancer types.…”
Section: Discussionsupporting
confidence: 93%
“…Zhu et al, In 2018, studying the CHD5 gene, showed that rs12564469‐rs9434711 was significantly associated with the prediction of hepatocellular carcinoma (HCC) 19 . A potential association was observed between the risk of HCC and CHD5 polymorphisms—rs2273032, rs12067480, and rs9434741—in a case–control study on the Chinese population 20 . In one study, rs1883603, rs9434741, and rs17436816 polymorphisms of the CHD5 gene in endometriosis were examined, and it was found that rs9434741 was significantly associated with endometriosis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…19 A case-control study confirmed the potential association between the risk of hepatocellular carcinoma and CHD5 polymorphisms rs2273032, rs12067480, and rs9434741 in the Chinese population. 20 Also, rs9434741 of the CHD5 gene was significantly associated with endometriosis in women. 21 The Hershlag study showed that the CHD5 rs538186680 was significantly higher in infertile males than in controls, so idiopathic causes of infertility may be associated with CHD5 disorders.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…CHD5 is one of the nine members of the CHD‐binding enzymes and belongs to the snf2 DNA helicase/methylasesuperfamily. CHD5 is composed of 42 exons that encode a 223 kDa protein – which encodes a protein of 1954 amino acids(Xiao et al, 2018). CHD5 is required for sperm development and defects in sperm chromatin density can lead to major problems in male fertility (Zhuang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%